2013
DOI: 10.1523/jneurosci.0173-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Signaling from the Parabrachial Nucleus Plays a Critical Role in Hypercapnic Arousal

Abstract: The mechanisms of arousal from apneas during sleep in patients suffering from obstructive sleep apnea (OSA) are not well understood. However, respiratory chemosensory pathways converge on the parabrachial nucleus (PB), which sends glutamatergic projections to a variety of forebrain structures critical to arousal including the basal forebrain, lateral hypothalamus, midline thalamus, and cerebral cortex. We tested the role of glutamatergic signaling in this pathway by developing an animal model for repetitive CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
236
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(251 citation statements)
references
References 41 publications
15
236
0
Order By: Relevance
“…7,26 On the other hand, electrocortical and behavioral arousal might be principally sustained by extrathalamic circuits including a corticostriatopallido(external)-cortical circuit, 24,25,33,34,[41][42][43] which would directly explain our findings, as well as the (glutamatergic) innervations emanating from the parabrachial/precoeruleus complex, which has been previously shown to be crucial for this process (but could not be assessed with the present technique). 18,44 In addition, we also found that the basal forebrain was (negatively) associated with the degree of sensory responsiveness of patients. This region is well known to play a causal role in the maintenance of behavioral and electrocortical arousal, and to induce a comalike state when extensively lesioned.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…7,26 On the other hand, electrocortical and behavioral arousal might be principally sustained by extrathalamic circuits including a corticostriatopallido(external)-cortical circuit, 24,25,33,34,[41][42][43] which would directly explain our findings, as well as the (glutamatergic) innervations emanating from the parabrachial/precoeruleus complex, which has been previously shown to be crucial for this process (but could not be assessed with the present technique). 18,44 In addition, we also found that the basal forebrain was (negatively) associated with the degree of sensory responsiveness of patients. This region is well known to play a causal role in the maintenance of behavioral and electrocortical arousal, and to induce a comalike state when extensively lesioned.…”
Section: Discussionsupporting
confidence: 52%
“…[45][46][47][48] One might therefore speculate that the degree of atrophy we observed in this region (50% of the region of interest, as compared to healthy volunteers) might not have been sufficient to induce the comalike state seen in animal models upon complete lesion of this region, 18 but might nonetheless have been sufficient to affect the mechanisms of fast cortical disinhibition. Future studies will have to address this possibility, as well as the exact relationship between the acute brainstem and basal forebrain comalike state observed in animal models, 18,44 acute brainstem coma in humans, 49 and chronic disorders of consciousness where some level of spontaneous arousal is recovered, in the absence of (self-)awareness. Third, paralleling postmortem examinations, 50 we have also shown in vivo that patients suffering from nontraumatic brain injury exhibit a more widespread and left-lateralized degree of thalamic atrophy, consistent with the well-known poorer prognosis associated with nontraumatic etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Another chemosensitive region, the retrotrapezoid nucleus, may be involved in sleep-wake regulation (Abbott et al 2013;Guyenet and Abbott 2013). Glutamatergic neurons of the parabrachial nucleus have also been implicated in CO 2 -induced arousal (Kaur et al 2013), although these neurons are not known to be intrinsically chemosensitive.…”
Section: Discussionmentioning
confidence: 99%
“…This reflex may be lost in diseases such as SIDS ) and SUDEP (Richerson and Buchanan 2011) and may be important in OSA apnea (Berthon-Jones and Sullivan 1984;Kaur et al 2013). In all of these diseases, hypoxia is encountered along with hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
“…81,95 In particular, there is evidence that glutamatergic neurons in the medial and lateral parabrachial nucleus play important roles in promoting spontaneous wakefulness and in mediating hypercapnic arousal from NREM sleep, respectively. 96 The parabrachial nucleus projects to the basal forebrain 95 and the thalamus, 97 which critically underlie the waking state, as well as to the orexin neurons. 88 These considerations suggest that efferent connections from the nucleus of the solitary tract to the parabrachial nucleus may promote awakening in response to increases in ABP.…”
Section: Integration Of the Neural And Cardiovascular Events Of Awakementioning
confidence: 99%